Evaluating HbA1c, BMI and Urinary Biochemistry as Risk Factors for Renal Tract Stones (Urolithiasis - M Farrukh Abbas Awan; Muhammad Ilyas; Malik, Aqsa; Muhammad Farooq (Journal of Liaquat University of Medical & Health Sciences, 2026)
OBJECTIVE: To evaluate the role of HbA1c, BMI and urinary parameters as predictors of renal stone formation. METHODOLOGY: This case-control study analyzed medical records of 300 patients with renal tract stones and 300 control subjects at the Ahmed Medical Complex in Rawalpindi from January to December 2024. Clinical data included demographics, BMI, HbA1c levels and urinary parameters (pH, citrate, Calcium). Statistical analysis was performed using t-tests, chi-square tests and logistic regression to identify significant predictors. RESULTS: Patients with urolithiasis had significantly higher BMI (28.1 ± 3.6 kg/m²) and HbA1c (7.2 ± 1.4%) than controls (p < 0.001). Urinary calcium excretion was elevated while citrate levels and urinary pH were lower in patients (p<0.001). Logistic regression identified HbA1c ?6.5% (OR: 2.3, p<0.001) and BMI >25 (OR: 1.7, p=0.002) as significant predictors. Patients with uric acid stones exhibited higher HbA1c levels than patients with calcium oxalate stones. CONCLUSION: Metabolic factors, particularly HbA1c and BMI, play a critical role in urolithiasis. Integrating glycemic control and weight management into preventive strategies could reduce the disease burden.